Ammonia emissions from dairy cattle buildings and outdoor concrete yards under the Mediterranean conditions of NW Portugal - Pereira, J. (2012)
Around 75% of European ammonia emissions comes from livestock production and emissions occur at all stages of manure management. Ammonia emissions have never been measured in commercial dairy cattle houses in Portugal. The objective of our study was to evaluate NH3 emissions for the main types of dairy cattle buildings naturally ventilated and outdoor concrete yards in NW Portugal.